Mortality risk among children admitted in a large-scale nutritional program in Niger, 2006. - Lapidus, N; Minetti, A; Djibo, A; Guerin, P; Hustache, S; Gaboulaud, V; Grais, R (Public Library of Science, 2009)
In 2006, the Medecins sans Frontieres nutritional program in the region of Maradi (Niger) included 68,001 children 6-59 months of age with either moderate or severe malnutrition, according to the NCHS reference (weight-for-height<80% of the NCHS median, and/or mid-upper arm circumference<110 mm for children taller than 65 cm and/or presence of bipedal edema). Our objective was to identify baseline risk factors for death among children diagnosed with severe malnutrition using the newly introduced WHO growth standards. As the release of WHO growth standards changed the definition of severe malnutrition, which now includes many children formerly identified as moderately malnourished with the NCHS reference, studying this new category of children is crucial.